FOREIGN COMMISSIONERS' IMPACT ON BOARD CHARACTERISTICS AND FIRM PERFORMANCE - Mahaputra, I Nyoman Kusuma Adnyana; Sudiartana, I Made; Bagiana, I Kadek; Primadona, Ida Ayu Lidya; Murti, Ni Putu Mita Ari (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2024)
This research addressed the problem of understanding how board composition influenced firm performance with a specific focus on the roles of female and foreign commissioners. Utilizing data from 122 manufacturing companies listed on the Indonesian Stock Exchange over the years 2019-2021. The research employed moderated regression analysis on 366 observations to examine this dynamic. The findings revealed that larger board sizes, as well as the presence of independent and female commissioners, positively affected firm performance. While foreign commissioners were found to enhance the positive impact of board size, they did not significantly moderate the effects of independent and female commissioners. These results highlighted the critical role of board diversity in enhancing corporate governance and firm performance, offering significant implications for global governance practices.